A Note on Errors in Time Series - Frisch, Ragnar (Quarterly Journal of Economics, 1939)
Journal Article A Note on Errors in Time Series Get access Ragnar Frisch Ragnar Frisch University of Norway Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 53, Issue 4, August 1939, Pages 639–640, https://doi.org/10.2307/1883286 Published: 01 August 1939